Pengembangan Buku Ajar Berbasis Strategi Pembelajaran Kontekstual Mata Kuliah Psikologi Olahraga - Uray Gustian (Universitas PGRI Semarang, 2019)
The study was conducted as an effort to find a learning method to improve student learning achievement which refers to the Kerangka Kualifikasi Nasional Indonesia (KKNI). Based on it, the development of textbooks that encourage students to construct knowledge and improve their ability to master theoretical concepts and problem solving research using research and development (R & D) methods. The stages in R & D research are modified (simplified) according to the research objectives. The stages of research and development used are 1) preliminary stage, 2) development phase, and 3 stages of dissemination. Participants consisted of 25 students at the time of the trial and 30 at the t test of effectiveness. The instruments used were questionnaires, questionnaires, questionnaires, and rubric ratings. Limited trial results obtained 76 (good), extensive trials 75 (good), and textbooks are feasible to use. The operational test shows that 23% of students are in the excellent category and 54% are in the good category. These results show that effective teaching materials improve student learning outcomes from previously 60% scored below the good category. The increase occurs because students are encouraged to be actively involved in finding material, finding the relationship between the material being studied and the actual conditions. Based on this, CTL-based textbooks are declared feasible and effective to be used in sports psychology courses